ADMINISTRATION OF EARLY POST-PARTUM ORAL DRENCH IN DAIRY COWS: EFFECTON METABOLIC PROFILE - R. Schallenberger Gonçalves; F. Cardoso; F. de Souza Guagnini; L. J. Reyes Castañeda; F. Gonzalez (Revista de la Facultad de Medicina Veterinaria y de Zootecnia)
Some prophylactic treatments have been proposed in high-yielding dairy cattle in order to minimize the effects of negative energy balance and some disturbances such as hypocalcaemia and ketosis. The objective of this study was to evaluate the effects of two doses of d rench within 24 h after calving on the metabolic profile and prevention of ketosis. a total of 48 cows from a herd in r io Grande do s ul state (southern Brazil) was used in the study. The animals were randomly selected and treated orally with d rench ( n = 32, propylene glycol, electrolytes and choline in 40 L of water) and water ( n = 16) used as control. Blood samples were collected by blood coccygeal venipuncture through a vacutainer plain system tubes. Biochemical determinations were performed in serum (albumin, urea, cholesterol, triglycerides, non-esterified fatty acids - ne F a -, calcium, phosphorus, magnesium, aspartate transaminase - as T- and gammaglutamyl- transferase -GGT-) and a cow-side determination of beta-hydroxybutyrate (BHB) was performed using the a bbot blood Precision Xtra system. a ll cows in the experiment had their milk production controlled. The d rench treatment produces a tendency to a better milk yield (32.5 vs 29.6 L/cow/day) and helps to prevent subclinical ketosis, as indicated by a lesser prevalence of subclinical ketosis (29.7% vs 37.2%) and mean values of BHB (1.19 vs 1.27 mmol/L) as well as a lesser lipolysis as indicated by ne F a values (509 vs 1.560 μmol/L). The other components of the metabolic profile did not have substantial effects between treatments. i n short, on the conditions of the present work, the d rench treatment is an effective management tool for prevention of subclinical ketosis and severe lipolysis.